Anticancer Potency of Methanol Extract from Terminalia catappa Leaves Using In Vitro and In Silico Methods - Warnasih, Siti; Mulyati, Ade Heri; Widiastuti, Diana; Zahra, Alita Chasanah; Sugita, Purwantiningsih; Ambarsari, Laksmi; Dianhar, Hanhan; Rahayu, Dyah Utami Cahyaning (Trends in Sciences, 2024)
Terminalia catappa is a plant with potential for application in various antioxidant, anti-inflammatory, antimetastatic and antitumor treatments. Therefore, this study aimed to investigate anticancer properties of methanol extract derived from T. catappa leaves, using both in vitro and in silico methods. The results showed that methanol extract had inhibition of HeLa and DU145 cell lines, with respective IC50 values of 352.50 and 954.99 μg/mL. LC-MS/MS analysis identified several active compounds within the extract, including catechin, quercetin, rutin, hirsutrin, loliolide, sesquiterpene, kaempferol, apigenin, cirsiliol, cirsimaritin and demethoxycurcumin, all of which had promising anticancer potential. These compounds performed well in the in silico test. According to computational predictions, rutin (−9.1 kcal/mol), catechin (−8.0 kcal/mol) and sesquiterpene (−8.2 kcal/mol) had higher binding affinity values than cisplatin and paclitaxel (−7.5 kcal/mol). Considering these results, the compounds were potentially anticancer agents through the inhibition of the Bcl-2 protein. Finally, T. catappa active compounds can be used as alternative candidates as a chemopreventive agent. HIGHLIGHTS Methanol extract from Terminalia catappa leaves could inhibit the proliferation of HeLa and DU145 cell lines. Methanol extract of Terminalia catappa leaves showed antiproliferative activity with IC50 of 352.50 μg/mL in HeLa and 954.99 μg/mL in DU145 cells. Rutin, a component of the methanol extract of Terminalia catappa leaves, showed a high affinity binding to Bcl-2 in silico. The extract could be beneficial to develop as a chemopreventive agent. GRAPHICAL ABSTRACT